2019
DOI: 10.5999/aps.2018.01473
|View full text |Cite
|
Sign up to set email alerts
|

Safe anesthesia for office-based plastic surgery: Proceedings from the PRS Korea 2018 meeting in Seoul, Korea

Abstract: There has been an exponential increase in plastic surgery cases over the last 20 years, surging from 2.8 million to 17.5 million cases per year. Seventy-two percent of these cases are being performed in the office-based or ambulatory setting. There are certain advantages to performing aesthetic procedures in the office, but several widely publicized fatalities and malpractice claims has put the spotlight on patient safety and the lack of uniform regulation of office-based practices. While 33 states currently h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Supporting the trend of plastic surgery cases being performed in the office, Osman and Shapiro [ 57 ] reported in their review that there were 72% of 17.5 million aesthetic procedures being done in the office-based setting annually. A common surgical technique is the use of tumescent lidocaine that has a somewhat large safety margin; however, fat embolism is a concern and has been associated with deaths [ 58 ].…”
Section: Outpatient Procedures By Specialtymentioning
confidence: 99%
“…Supporting the trend of plastic surgery cases being performed in the office, Osman and Shapiro [ 57 ] reported in their review that there were 72% of 17.5 million aesthetic procedures being done in the office-based setting annually. A common surgical technique is the use of tumescent lidocaine that has a somewhat large safety margin; however, fat embolism is a concern and has been associated with deaths [ 58 ].…”
Section: Outpatient Procedures By Specialtymentioning
confidence: 99%
“…In general, procedural sedation can be helpful in providing a comfortable patient experience in this setting. In the procedures described in Table 1, sedation is often not a requirement but is commonly combined with local anesthetic to make the experience more comfortable and is generally considered safe 2,11,12 . Personnel, equipment, and training considerations for appropriate office‐based anesthesia are described further in later sections.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reviews over the past ten years showed emerging trends towards patient safety in the office-based surgical (OBS) centers and ambulatory surgery centers (ASC) [1][2][3][4][5]. Common OBS procedures at that time included abdominoplasty, orthopedic surgery, plastic surgery, pain management procedures, and dental surgery, with infrequent complications like venous thromboembolism (VTE), hospital admissions, and rarely, death [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…Early work was put into developing criteria for proper patient selection for the office [3]. Accreditation of offices and ambulatory facilities were positively correlated with improved patient outcomes [4]. Considering the longstanding safety paradigms established in cosmetic surgery and dentistry, in this analysis, we conducted an evidenced based narrative review of recent literature describing the latest safety profiles, financial impacts, and controversies from the established and emerging specialties in the OBS setting.…”
Section: Introductionmentioning
confidence: 99%